Selectively targeting the AdipoR2-CaM-CaMKII-NOS3 axis by SCM-198 as a rapid-acting therapy for advanced acute liver failure - Rui Wang; Youwei Chen; Jiazhen Han; Huikang Ye; Huiran Yang; Qianyan Li; Yizhen He; Boyu Ma; Junjie Zhang; Yanli Ge; Zhe Wang; Bo Sun; et al. (Nature Communications)
Abstract Acute liver failure (ALF) is a hepatology emergency with rapid hepatic destruction, multiple organ failures, and high mortality. Despite decades of research, established ALF has minimal therapeutic options. Here, we report that the small bioactive compound SCM-198 increases the survival of male ALF mice to 100%, even administered 24 hours after ALF establishment. We identify adiponectin receptor 2 (AdipoR2) as a selective target of SCM-198, with the AdipoR2 R335 residue being critical for the binding and signaling of SCM-198-AdipoR2 and AdipoR2 Y274 residue serving as a molecular switch for Ca2+ influx. SCM-198-AdipoR2 binding causes Ca2+ influx and elevates the phosphorylation levels of CaMKII and NOS3 in the AdipoR2-CaM-CaMKII-NOS3 complex identified in this study, rapidly inducing nitric oxide production for liver protection in murine ALF. SCM-198 also protects human ESC-derived liver organoids from APAP/TAA injuries. Thus, selectively targeting the AdipoR2-CaM-CaMKII-NOS3 axis by SCM-198 is a rapid-acting therapeutic strategy for advanced ALF.